Autogenous sealing of a cavity in bentonite clay: an x-ray computerised tomography study. Issue 4 (1st December 2021) - Gao, Y.; El-Zein, A.; Airey, D.; Proust, G.
Abstract : Autogenous closure of cracks in clay during wet−dry cycles is usually observed through digital photography or x-ray, or inferred from changes in hydraulic conductivity. Samples in almost all experimental studies of clay self-sealing carry networks of cracks, making it challenging to control initial conditions of healing or to separate processes operating over a single crack from those pertaining to interaction between cracks. Furthermore, most observational studies are based on before-and-after images with little sense of the pace of crack closure. This paper reports a set of x-ray computerised tomography observations of a single artificial cylindrical hole, as a proxy for a crack, in consolidated, close-to-saturation bentonite samples, undergoing further hydration. The sample is scanned at different times and the scans analysed by image processing. The results show that water chemistry, pre-consolidation pressure and vertical boundary conditions all significantly affect the pace and extent of hole closure. The pace of hole closure is found to follow a logarithmic function when the sample is unconstrained vertically. Autogenous closure appears to be due mostly to osmotic swelling. This suggests that the latter may form the basis for developing constitutive relationships and evolution functions for sealing of cracks in swelling clay undergoing wet−dry cycles.